أثر الشمول المالي على النمو الاقتصادي في دول شمال إفريقيا 2019- دراسة قياسية تحليلية للفترة 2004: The Impact Of Financial Inclusion On Economic Growth In The North Africa Contries An Empirical and Analytical Study During the Period 2004-2019 - بن منصور نجيم (Journal of North African Economies, 2025)
This paper aims to measure and analyze the effect of the financial inclusion on the economic growth in Algeria, Morocco, Tunisia,Egypt during the period(2004-2019). The econometric model used in this study is the panel auto-regressive distributed lags model ( PANEL ARDL). The study uses the Principal Components Analysis to determine the financial inclusion based on the Number of commercial bank branches and Number of automated teller machines ATMs, per 1,000 km2; and the Number of commercial bank branches and Number of automated teller machines ATMs, per 100.000 Adults ; the GDP to express economic growth. The study also uses the variables of investment, population and exchange rate as the control variables. The main finding of this research is the existence of long-term positive relation between the Financial inclusion and the economic growth in the countries studied, where the probability was significant less than 5%, as the change in the financial inclusion index by one point leads to a change in the economic growth by 2.7 points. while, the test of causality in the short and long run demonstrated that there is no causal relationship between financial inclusion and economic growth.